Utilizing Graphic Design Trends To Reimagine Saudi Culture Identity - M. Hassan , Shaimaa; Al-Dajani , Thekra A. (Journal of Ecohumanism, 2025)
As the Kingdom moves towards renaissance under Vision 2030, and the opportunity to harness its cultural assets to enhance a vibrant community and a prosperous economy, design has played a role in preserving culture and redefining cultural experiences in contemporary contexts. Design is also characterized by its ability to transform and revive cultural practices to change and modify perceptions, generate and disseminate knowledge, and create new value through organizing the experience. The problem of this research is based on the main question of: can the graphic design trends reimagine Saudi heritage; as a step to preserving and redefining cultural? The objective of this study is to explore how contemporary graphic design trends, specifically Organized Chaos and Maximalism, can be used to reinterpret and preserve Saudi cultural heritage. It aims to document and showcase the aesthetic and artistic dimensions of Saudi heritage through bold and modern visual representations, emphasizing oral storytelling and traditional attire and enhance national identity, engage younger generations, and create a cultural brand that resonates with both local and global audiences. The study evaluated the effectiveness of ten graphic design approaches by gathering feedback from 10 experts. Design 3 and Design 8 received the highest quality index scores of 90.00, reflecting their strong visual impact, unique concepts, and effective use of cultural elements. The highest-ranked aspect was innovation, with a score of 83.33, followed by aesthetics at 82.72 and functionality at 82.28. Despite the lack of statistically significant differences in specialists’ evaluations, certain designs were perceived as stronger than others. Design 6 ranked lowest in the aesthetic aspect due to its unbalanced structure and weak visual impact. Design 4 received the lowest overall ranking with a score of 74.33, attributed to its lack of clarity and weaker adherence to design principles. Similarly, Design 1 had the lowest innovation ranking at 76.00, with recommendations for concept reinterpretation, better element distribution, and bolder color choices.